2001
DOI: 10.1007/s101890170090
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of anionic polyelectrolytes to dioctadecyldimethylammonium bromide monolayers

Abstract: Monolayers of dioctadecyldimethylammonium bromide (DODA) at the air/water interface were used as model for charged surfaces to study the adsorption of anionic polyelectrolytes. After spreading on a pure water surface the monolayers were compressed and subsequently transferred onto a polyelectrolyte solution employing the Fromherz technique. The polyelectrolyte adsorption was monitored by recording the changes in surface pressure at constant area. For poly(styrene sulfonate) and carboxymethylcellulose the plot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…The experimental results [33][34][35][36] were fitted using the Johnson-Mehl-Avrami equation (JMA), given by…”
Section: Resultsmentioning
confidence: 99%
“…The experimental results [33][34][35][36] were fitted using the Johnson-Mehl-Avrami equation (JMA), given by…”
Section: Resultsmentioning
confidence: 99%
“…However, a reduction of π c with the molecular weight of PSS has been observed. It cannot be attributed to electrostatic forces as described by the DLVO theory [18,19]. π c decreases on increase of the molecular weight, until the contour length corresponds to the persistence length, then π c is independent of the molecular weight.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, the surface charge density of the monolayer increases by a factor of two. The adsorbed PEs influence the interactions between the lipid molecules, which can best be investigated by exploring the LE/LC phase transition [18][19][20] PEs in salt-free solution have a much larger persistence length than neutral polymers [21]. If the contour length L K is smaller than the persistence length L P (L K  L P ) then the polymer is approximated as an elastic rod.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been observed that some water-soluble materials can also form stable and well-organized Langmuir monolayer at the air-water interface [4][5][6][7]. It was first observed by Vollhardt et al in 1997 [8] and later discussed in detail in another two papers [9,10].…”
Section: Introductionmentioning
confidence: 95%
“…Menzel et al reported the reaction kinetics and adsorption of poly(styrene sulfonate) and carboxymethylcellulose sodium salt onto a preformed dioctadecyldimethylammonium bromide monolayer [6,7]. Adsorption of poly(NIPAM) on the preformed pentadecanoic acid (PDA) monolayer was demonstrated by Kawaguchi et al [5].…”
Section: Introductionmentioning
confidence: 97%